Optimizing energy efficiency and thermal comfort in building green retrofit - Li, Qing (2022)
Building green retrofit offers significant opportunities for enhancing energy efficiency and achieving green development goals. However, a conflicting criterion exists between energy conservation and thermal comfort improvement when making optimal design solutions for building retrofit. This study presents a simulation-based energy-comfort optimization model to facilitate evaluating various design alternatives and balancing multiple objectives in building green retrofit. A building simulation model is first established to measure energy consumption and comfort level. Then, a multi-objective optimization method (response surface method) is employed to identify critical building parameters and generates a set of alternative plans for building retrofit based on green building standards. After that, optimal design solutions with trade-offs between thermal comfort and energy demand are obtained. A school building in Wuhan city of China is chosen as a case to validate the developed model, and ten building parameters pertaining to energy demand and environmental comfort are considered in the optimization process. The results show that four parameters are significantly sensitive to energy efficiency and thermal comfort, including insulation thickness of the external wall, the heat transmission coefficient of the roof, solar heat gain coefficient of the external window, and window to wall ratio. The optimal combination of four parameters approximately produces 4 % of energy savings, as well as an improving level of environmental comfort. The study benefits designers and construction managers to determine optimal solutions for building retrofit to achieve better energy efficiency and comfort in green building development.